Genetic disruption of Ano5 in mice does not recapitulate human ANO5-deficient muscular dystrophy. Issue 1 (December 2015) - Xu, Jing; El Refaey, Mona; Xu, Li; Zhao, Lixia; Gao, Yandi; Floyd, Kyle; Karaze, Tallib; Janssen, Paul; Han, Renzhi
Abstract Background Anoctamin 5 (ANO5 ) is a member of a conserved gene family (TMEM16), which codes for proteins predicted to have eight transmembrane domains and putative Ca2+ -activated chloride channel (CaCC) activity. It was recently reported that mutations in this gene result in the development of limb girdle muscular dystrophy type 2L (LGMD2L), Miyoshi myopathy type 3 (MMD3), or gnathodiaphyseal dysplasia 1 (GDD1). Currently, there is a lack of animal models for the study of the physiological function ofAno5 and the disease pathology in its absence. Results Here, we report the generation and characterization of the firstAno5 -knockout (KO) mice. Our data demonstrate that the KO mice did not present overt skeletal or cardiac muscle pathology at rest conditions from birth up to 18 months of age. There were no significant differences in force production or force deficit following repeated eccentric contractions between wild type (WT) and KO mice. Although cardiac hypertrophy developed similarly in both KO and WT mice after daily isoproterenol (ISO, 100 mg/kg) treatment via intraperitoneal injection for 2 weeks, they were functionally indiscernible. However, microarray analysis identified the genes involved in lipid metabolism, and complement pathways were altered in the KO skeletal muscle. Conclusions Taken together, these data provide the evidence to show that genetic ablation ofAno5 in C57BL/6J mice does not cause overt pathology in skeletal and cardiac muscles, butAno5 deficiency may lead to altered lipid metabolism and inflammation signaling.